2022
DOI: 10.3389/fsoil.2022.979246
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizae helper bacteria for managing the mycorrhizal soil infectivity

Abstract: Arbuscular mycorrhizal fungi are major components of soil microbiota and mainly interact with other microorganisms in the rhizosphere. Mycorrhiza establishment impacts the plant physiology and some nutritional and physical properties of the rhizospheric soil. These effects alter the development of the root or mycorrhizas resulting from the activity of soil microorganisms. The rhizosphere of mycorrhizal plants (mycorrhizosphere), is inhabited by large microbial activities responsible for several key ecosystem p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
(43 reference statements)
0
5
0
3
Order By: Relevance
“…Normally, BMs promote plant growth either by directly facilitating nutrient uptake (as biofertilizers) or by modulating (stimulating) plant hormone levels (Russo et al, 2022). Improved nutrient uptake is frequent in the case of soil BMs that do not act as endophytes (Nasslahsen et al, 2022), although it was reported that B. bassiana might enhance nutrient availability, particularly soluble phosphate (Barra-Bucarei et al, 2019a). Endophytization is more likely to activate plant hormones, especially those involved in plant growth and development (Waadt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, BMs promote plant growth either by directly facilitating nutrient uptake (as biofertilizers) or by modulating (stimulating) plant hormone levels (Russo et al, 2022). Improved nutrient uptake is frequent in the case of soil BMs that do not act as endophytes (Nasslahsen et al, 2022), although it was reported that B. bassiana might enhance nutrient availability, particularly soluble phosphate (Barra-Bucarei et al, 2019a). Endophytization is more likely to activate plant hormones, especially those involved in plant growth and development (Waadt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…MHB juga diketahui menghasilkan beberapa senyawa volatil maupun non volatil seperti CO2, tiamin dan 2-methylisoborneol yang meregulasi germinasi spora (Nasslahsen et al, 2022;Guarnizo et al, 2023). Namun demikian informasi tentang pengujian kemampuan FMA maupun MHB untuk meningkatkan pertumbuhan bibit kentang secara in vitro dalam menghasilkan hormon, asam organik maupun enzim masih terbatas (Minemba et al, 2019).…”
Section: Selanjutnyaunclassified
“…Pertumbuhan Planlet Kentang yang Diberi FMA dan MHB Hasil pengukuran terhadap pertumbuhan planlet kentang pada media MS yang diberi perlakuan FMA dan MHB menunjukkan bahwa perlakuan kontrol pertumbuhannya lebih rendah yang diamati melalui bobot segar tanaman (Tabel 3). Tinggi tanaman pada kultur tempat akar tumbuh merupakan kriteria aktivitas stimulan pertumbuhan (Nasslahsen et al, 2022) Temuan penelitian ini mengkonfirmasi bahwa prekursor fitohormon dihasilkan oleh kultur yang diberi bakteri dan eksudat akar dari tanaman merupakan sumber triptofan (Hajare et al, 2021).…”
Section: Rancangan Percobaanunclassified
See 1 more Smart Citation
“…Bacteria that function actively as mycorrhizal fungal enhancers are found in (1) the Proteobacteria, specifically within the bacteria genera: Pseudomonas, Agrobacterium, Azospirillum, Azotobacter, Burkholderia, Bradyrhizobium, Enterobacter, Klebsiella and Rhizobium species, (2) the Actinobacteria including Rhodococcus, Streptomyces and Arthrobacter sp., and (3) the Firmicutes that include Bacillus, Brevibacillus and Paenibacillus sp. (Martin, 2016;Nasslahsen et al, 2022). These mycorrhizal helper bacteria may also perform several other functions not limited to enhancing AMF, such as plant growth promoting activities through the production of phytohormones (Sangwan and Prasanna, 2022), and they are widespread in tea garden soils.…”
Section: Bacterial Communities In Soils Of Tea Gardensmentioning
confidence: 99%